# Composite Functions Test

Approved & Edited by ProProfs Editorial Team
The editorial team at ProProfs Quizzes consists of a select group of subject experts, trivia writers, and quiz masters who have authored over 10,000 quizzes taken by more than 100 million users. This team includes our in-house seasoned quiz moderators and subject matter experts. Our editorial experts, spread across the world, are rigorously trained using our comprehensive guidelines to ensure that you receive the highest quality quizzes.
| By Vicki Barr
V
Vicki Barr
Community Contributor
Quizzes Created: 14 | Total Attempts: 2,266
Questions: 10 | Attempts: 819

Settings

Learning mathematics can be difficult, but we are here to make it fun. Try our composite functions test to understand more about this mathematical concept. In mathematics, composite functions occur when two functions, a and b, make a new function, h, in such a way that h(x) = a(b(x)). Get ready to practice and get ahead in your maths class! Let's learn maths in a fun way! Remember to collect your scorecard after you've completed the quiz. All the best!

• 1.

• 2.

### k(g(2))

Explanation
The expression k(g(2)) means that the function g is applied to the number 2, and then the result is passed as an input to the function k. Since the answer is -2, it suggests that the function g(2) evaluates to -2, and then this value is passed to the function k, which also evaluates to -2. Therefore, the overall expression k(g(2)) simplifies to -2.

Rate this question:

• 3.

• 4.

### f(h(3))

Explanation
The given expression f(h(3)) means that the function h is applied to the number 3, and then the result of that is passed as an input to the function f. Since the answer is -84, it implies that the function h(3) evaluates to -84, and then f(-84) evaluates to -84 as well.

Rate this question:

• 5.

• 6.

### g(h(2))

Explanation
The given expression, g(h(2)), means that the function h is applied to the number 2 first, and then the result of h(2) is passed as an input to the function g. The final result is -25.

Rate this question:

• 7.

• 8.

### In the following equation f(x) = x+3, find the value f(-2).

• A.

0

• B.

1

• C.

5

• D.

-1

B. 1
Explanation
To find the value of f(-2), we substitute -2 into the equation f(x) = x+3. So, f(-2) = -2 + 3 = 1. Therefore, the correct answer is 1.

Rate this question:

• 9.

### In equation f(x)= -3x+7 and g(x)=2x2 - 8, can you find the value of f(g(x))?

• A.

F(g(x))= -6x2+31

• B.

F(g(x))= -5x2+30

• C.

F(g(x))=22x2-54x+62

• D.

F(g(x))=5x2-72x3

A. F(g(x))= -6x2+31
Explanation
To find the value of f(g(x)), we substitute g(x) into the equation for f(x). Since g(x) = 2x^2 - 8, we substitute this expression into f(x) to get f(g(x)) = -3(2x^2 - 8) + 7. Simplifying this equation, we get f(g(x)) = -6x^2 + 24 + 7 = -6x^2 + 31. Therefore, the correct answer is f(g(x)) = -6x^2 + 31.

Rate this question:

• 10.

### In the equations g(x) = 2x - 5; h(x) = 4x + 5. Can you find (g - h)(3)?

• A.

0

• B.

-16

• C.

16

• D.

18

B. -16
Explanation
To find (g - h)(3), we substitute 3 into both g(x) and h(x) and subtract the results. Substituting 3 into g(x) gives us g(3) = 2(3) - 5 = 6 - 5 = 1. Substituting 3 into h(x) gives us h(3) = 4(3) + 5 = 12 + 5 = 17. Subtracting g(3) from h(3) gives us 17 - 1 = 16. Therefore, the correct answer is 16.

Rate this question:

Quiz Review Timeline +

Our quizzes are rigorously reviewed, monitored and continuously updated by our expert board to maintain accuracy, relevance, and timeliness.

• Current Version
• May 17, 2023
Quiz Edited by
ProProfs Editorial Team
• Oct 08, 2014
Quiz Created by
Vicki Barr

Related Topics